Density, viscosity, physical CO2 diffusivity, and CO2 absorption capacity of novel blended N-methyl-4-piperidinol and piperazine solvent. (November 2021) - Apaiyakul, Rattanaporn; Ranong, Pipat Na; Kiattinirachara, Thanthip; Posoknistakul, Pattaraporn; Pakchotanon, Pet; Jiraratananon, Ratana; Tontiwachwuthikul, Paitoon; Sema, Teerawat
Abstract: In the present work, novel blended piperazine (PZ) and N-methyl-4-piperidinol (MPDL) solvent was investigated in terms of density, viscosity, physical diffusivity of CO2, and CO2 absorption capacity. Density and viscosity were measured over PZ/MPDL concentration ratios of 5/25, 10/20, and 15/15 %wt. and temperatures of 313, 323, and 333 K. Physical diffusivity of CO2 was calculated based on viscosity data by the modified Stokes–Einstein equation. Lastly, CO2 absorption capacity (mol CO2 /mol amine) was experimentally determined in a temperature-controlled absorption reactor at 313 K and 10% v/v CO2 . The results showed that density and viscosity of novel blended PZ-MPDL solvent increased as PZ concentration ratio increased and decreased as temperature increased. On another hand, physical diffusivity of CO2 decreased as PZ concentration ratio increased and increased as temperature increased. Based on the physical properties data (i.e., density, viscosity, and physical diffusivity of CO2 ), it can be summarized that the studied physical properties of PZ-MPDL were in the same ranges with those of conventional amine solvents. Additionally, it was found that CO2 absorption capacity of PZ-MPDL can be improved by increasing PZ concentration ratio. As a result, 15/15 %wt. PZ-MPDL showed the highest CO2 absorption capacity (0.741 mol CO2 /mol amine) among the three studied concentrations. It also possessed 49% higher CO2 absorption capacity than the conventional benchmarking 30 %wt. monoethanolamine (MEA).